APLIKASI THEORY OF PLANNED BEHAVIOR UNTUK PENGAMBILAN KEPUTUSAN PEMBELIAN LAPTOP LENOVO - Simanihuruk, Peran (Sekolah Tinggi Ilmu Ekonomi Graha Kirana, 2024)
The aim of this research is to investigate the application of the Theory of Planned Behavior in the decision-making process of purchasing Lenovo laptops among students. The population consisted of all students from the Faculty of Economics and Business at the Catholic University of Santo Thomas Medan for the Academic Year 2022/2023, with a sample size of 96 students. Data collection was conducted through questionnaires, and the analysis technique utilized descriptive analysis based on formulas within the Theory of Planned Behavior. The research findings show that students have a generally positive attitude towards Lenovo laptops, with beliefs about the laptop's attributes and consequences being moderately positive. The attitude score is also positive, with an average of 1.208. Normative beliefs and motivation to comply with referent groups are positive but have a lower influence on behavior, reflected in a subjective norm score of 0.087. Perceived behavioral control is positive, with a belief score of 0.415 and ease of control at 0.467. The behavioral intention equation reveals that students' purchase behavior of Lenovo laptops is mainly influenced by their attitude (44%), followed by perceived behavioral control (40%), and subjective norm (16%). Lenovo laptop manufacturers are advised to enhance attributes deemed important by students to improve competitiveness and increase the influence of subjective norms and perceived behavioral control by offering benefits and convenience to their customers. The aim of this research is to investigate the application of the Theory of Planned Behavior in the decision-making process of purchasing Lenovo laptops among students. The population consisted of all students from the Faculty of Economics and Business at the Catholic University of Santo Thomas Medan for the Academic Year 2022/2023, with a sample size of 96 students. Data collection was conducted through questionnaires, and the analysis technique utilized descriptive analysis based on formulas within the Theory of Planned Behavior. The research findings show that students have a generally positive attitude towards Lenovo laptops, with beliefs about the laptop's attributes and consequences being moderately positive. The attitude score is also positive, with an average of 1.208. Normative beliefs and motivation to comply with referent groups are positive but have a lower influence on behavior, reflected in a subjective norm score of 0.087. Perceived behavioral control is positive, with a belief score of 0.415 and ease of control at 0.467. The behavioral intention equation reveals that students' purchase behavior of Lenovo laptops is mainly influenced by their attitude (44%), followed by perceived behavioral control (40%), and subjective norm (16%). Lenovo laptop manufacturers are advised to enhance attributes deemed important by students to improve competitiveness and increase the influence of subjective norms and perceived behavioral control by offering benefits and convenience to their customersKeywords: Purchasing Decision Making, Subjective Norms, Perceived Behavioral